Unsteady stagnation point flow past a permeable stretching/ shrinking Riga plate in Al2O3-Cu/H2O hybrid nanofluid with thermal radiation - Zainal, Nurul Amira; Nazar, Roslinda; Naganthran, Kohilavani; Pop, Ioan (Emerald Group Holdings Ltd., 2022)
Purpose – The investigation of fluid flow and heat transfer is incredibly significant in the present era, particularly in the engineering and manufacturing industries. Hence, this study aims to concern with analysing the unsteady stagnation point flow towards a permeable stretching/shrinking Riga plate of Al2O3- Cu/H2O. The effect of thermal radiation on the boundary layer flow is also taken into account. Design/methodology/approach – The multi-variable differential equations with partial derivatives are transformed into third-order and second-order differential equations by applying appropriate transformations. The reduced mathematical model is solved in the MATLAB system by using the bvp4c procedure. This solution approach is capable of producing multiple solutions once the necessary assumptions are provided. Findings – The results of various control parameters were analysed, and it has been observed that raising the solution viscosity from 0% to 0.5% and 1% improves the coefficient of skin friction and thermal conductivity by almost 1.0% and 1.9%. Similar response and observation can be witnessed in the addition of modified Hartmann number where the highest values dominate about 10.7% improvement. There is a substantial enhancement in the heat transfer rate, approximately 1.8% when the unsteadiness parameter leads around 30% in the boundary layer flow. In contrast, the increment in thermal radiation promotes heat transfer deterioration. Further, more than one solution is proven, which invariably leads to a stability analysis, which validates the first solution’s feasibility. Originality/value – The present results are new and original for the study of flow and heat transfer on unsteady stagnation point flow past a permeable stretching/shrinking Riga plate in Al2O3-Cu/H2O hybrid nanofluid with thermal radiation